In the name of charity: Political connections and strategic corporate social responsibility in a transition economy - Lin, Karen Jingrong; Tan, Jinsong; Zhao, Liming; Karim, Khondkar (Journal of Corporate Finance, 2015)
This study investigates whether firms in China use corporate social responsibility (CSR) to build political networks and, if so, how such CSR decisions affect firm performance. We bypass the empirical difficulty of measuring the value of political networks by using an event study approach. Specifically, we examine how abrupt termination of existing political connections caused by replacement of city mayors affect Chinese listed companies' CSR choices. We find that when a mayor is replaced, the level of and the propensity for CSR activity increase. Such increases are more prominent in firms for which political connections are more valuable, namely, nonstate-controlled firms, smaller firms, and firms operating in cities ruled by more corrupt government. In addition, we find that firms that spend resources to bond with a new government via CSR activities are rewarded: these firms receive higher levels of government subsidies or have a greater propensity to receive future government subsidies. These firms also outperform firms that do not invest in political networking via CSR. Our study adds direct evidence to how and through what channel CSR affects firm performance. We also contribute to the CSR literature on politically motivated CSR strategies.